The Female Urinary Microbiota in Urgency Urinary Incontinence - Pearce, Meghan M. (Am J Obstet Gynecol, 2015)
OBJECTIVES: To characterize the urinary microbiota in women planning treatment for urgency urinary incontinence and to describe clinical associations with urinary symptoms, urinary tract infection and treatment outcomes. STUDY DESIGN: Catheterized urine samples were collected from female multi-site randomized trial participants without clinical evidence of urinary tract infection and 16S rRNA gene sequencing was used to dichotomize participants as either DNA sequence-positive or sequence-negative. Associations with demographics, urinary symptoms, urinary tract infection risk, and treatment outcomes were determined. In sequence-positive samples, microbiotas were characterized on the basis of their dominant microorganisms. RESULTS: Over half [51.1% (93/182)] of the participants’ urine samples were sequence-positive. Sequence-positive participants were younger (55.8 vs. 61.3, p=0.0007), had a higher body mass index (33.7 vs. 30.1, p=0.0009), had a higher mean baseline daily urgency urinary incontinence episodes (5.7 vs. 4.2, p<0.0001), responded better to treatment (decrease in urgency urinary incontinence episodes −4.4 vs. −3.3, p=0.0013) and were less likely to develop urinary tract infection (9% vs. 27%, p=0.0011). In sequence-positive samples, eight major bacterial clusters were identified; seven clusters were dominated by a single genus, most commonly Lactobacillus (45%) or Gardnerella (17%), but also other taxa (25%). The remaining cluster had no dominant genus (13%). CONCLUSIONS: DNA sequencing confirmed urinary bacterial DNA in many women without signs of infection and with urgency urinary incontinence. Sequence status was associated with baseline urgency urinary incontinence episodes, treatment response and post-treatment urinary tract infection risk.